2020
DOI: 10.1111/jfpe.13485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot air, vacuum infrared, and vacuum microwave dryers on the drying kinetics and quality characteristics of orange slices

Abstract: The present study aimed to dry orange slices at 50, 60, and 70 C using vacuum microwave dryer (VMD), vacuum infrared dryer (VID), and tray dryer (TD) and to compare the effects of different drying techniques on drying kinetics and product qualities. For this purpose, drying kinetics, total phenolic content, vitamin C, pH, total titratable acidity, bulk density, and color values of dried orange slices were evaluated. The VMD significantly increased the drying rates and the effective moisture diffusivities of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 75 publications
(132 reference statements)
2
54
1
4
Order By: Relevance
“…This may be due to case-hardening that obstructed the moisture transfer throughout the ginkgo seeds drying process, and this attests to why it had the least drying rate (Figure 1b) amongst the heat-dried ginkgo seeds (ID, HAD, and PVD). The lowest Finally, mathematical modeling's' of the drying processes were applied to the ginkgo seeds drying process since it is essential in designing and optimizing, as they have been widely utilized to define foods' drying characteristics (Bozkir, 2020;Ertekin & Firat, 2017;Jahanbakhshi et al, 2020). The drying kinetics of ginkgo seeds were represented using three thin-layer models.…”
Section: Drying Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to case-hardening that obstructed the moisture transfer throughout the ginkgo seeds drying process, and this attests to why it had the least drying rate (Figure 1b) amongst the heat-dried ginkgo seeds (ID, HAD, and PVD). The lowest Finally, mathematical modeling's' of the drying processes were applied to the ginkgo seeds drying process since it is essential in designing and optimizing, as they have been widely utilized to define foods' drying characteristics (Bozkir, 2020;Ertekin & Firat, 2017;Jahanbakhshi et al, 2020). The drying kinetics of ginkgo seeds were represented using three thin-layer models.…”
Section: Drying Kineticsmentioning
confidence: 99%
“…These can be solved mainly by artificial drying processes such as hotair, microwave, vacuum, infrared, and freeze-drying, which can shorten drying time, develop desirable products and increase food bioactivity Bozkir, 2020;Kaveh, Jahanbakhshi, Taghinezhad, & Abbaspour-gilandeh, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lightness (L * ), redness (a * ), and yellowness (b * ) values were determinate using a colorimeter (CR-10; Konica Minolta, Japan). Total color difference (ΔE), total chroma (ΔC), and Hue angle (H ) were calculated according to Formulas (7), (8), and (9), respectively (Bozkir, 2020).…”
Section: Colormentioning
confidence: 99%
“…It was reported that the sweet potato slices treated with 0.5:1.0% KMS and citric acid at 50°C has shown optimal condition for predict drying kinetics. Bozkir (2020) used three different types of dryers, namely vacuum microwave, tray type and vacuum infrared dryers for drying orange samples at 50°C ‐70°C drying air temperature. It was observed that the Page and Logarithmic mathematical model gave better agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%